Legal Protection for Indonesian Migrant Workers in International Human Trafficking Syndicates - Indradewi, Astrid Athina; Ginting, Yuni Priskila (LPPM Universitas Ekasakti Padang, 2024)
Human rights are inherent in human dignity and are essential for the protection of individuals and society. The Indonesian government has established human rights rules under the Universal Declaration of Human Rights, but human rights violations continue, particularly in the context of international human trafficking. The Indonesian Human Trafficking Crime Task Force has received 757 reports, with victims coerced into working as child laborers, commercial sex workers, illegal immigrants, and ship crew members. The Indonesian government regulates migrant workers through Law 18/2017, but many are mistreated and exploited by foreign employers. This research uses juridical-normative legal research to examine literature, ideas, and laws to propose solutions. It employs conceptual and statutory approaches. Through this research, it is found that to strengthen migrant worker protection, governments must collaborate, tighten regulations, offer guidance, and establish efficient channels for handling grievances. The International Convention on the Protection of the Rights of Migrant Workers and Their Families is crucial for ensuring the rights and protection of migrant workers, but its implementation faces challenges.